The Effect of Competitive CrossFit Exercises Using the Station Method on Developing Speed-Based Strength and Psychological Endurance among Middle School Students (Damu Journal of Sport Sciences, 2025)
The research problem was identified as the lack of modern, competitive methods among middle school students using the station method, which contribute to raising the level of physical and psychological fitness of the student. The research aims to develop a set of competitive CrossFit exercises using the station method to develop speed-based strength and psychological endurance for middle school students, and to examine the effect of competitive CrossFit exercises using the station method on developing speed-based strength and psychological endurance for middle school students. The researcher used the single experimental group method with pre- and post-tests. The process of determining the sample chosen by the researcher according to his research problem is one of the important steps to achieve his goals and hypotheses. The researcher chose his research sample from the students of Al-Hillah Intermediate School for Boys for the academic year (2024-2025), numbering (36) students, with (12) players for each stage. After that, the sample was tested with pre-tests for the researched (physical and psychological) abilities. After that, competitive CrossFit exercises were applied using the stations method, where the application period lasted two months, with (3) lessons per week, and the total curriculum amounted to (24) sessions. The researcher concluded that competitive CrossFit exercises using the stations method had a direct impact on developing the distinctive speed strength and psychological endurance of intermediate school students in Babil Governorate.